Protein interactions and subcellular localization in S-RNase-based self-incompatibility. (22nd March 2010) - Sims, Thomas L.; Patel, Avani; Shrestha, Pratima
Abstract : The recent identification of several proteins playing key roles in S -RNase-based gametophytic self-incompatibility has led both to a greater understanding of the molecular biology of this response, as well as to questions regarding the precise mechanism by which compatible pollen tubes are recognized and accepted. A proposed variant SCF SLF (where SCF is SSK1/cullin/F-box and SLF is S -locus F-box) ubiquitin ligase complex is thought to play a central role in recognizing and inhibiting non-self S -RNases, but the exact role of ubiquitination remains unclear. How the possible sequestration of non-self S -RNases in a pollen vacuolar compartment can be reconciled with the need for protein interaction between S -RNase and the SCF SLF complex needs to be determined. Current work to answer these questions focuses on more precisely defining quantitative protein interactions and subcellular localization of proteins involved in S -RNase-based gametophytic self-incompatibility.